IMPROVING THE ABILITY TO IDENTIFY REGULAR AND IRREGULAR VERBS THROUGH READING NARRATIVE TEXTS - Afifah; Kamaruddin , Abdul (e-Journal of ELTS (English Language Teaching Society), 2023)
The purpose of this article is to prove that the use of reading narrative texts can improve the ability of grade eight students of SMPN 3 Palu to identify regular and irregular verbs. The method used is a true-experimental design in which there were two classes involved – experimental and control class. The question of this research is “Can the use of reading narrative texts improve the ability of grade eight students of SMPN 3 Palu in identifying regular and irregular verbs?” The sample of this research is the grade eight students of class I and J of SMPN 3 Palu. Class VIII I became the experimental group, and class VIII J became the control group. Based on hypothesis testing done, by using 0.05 level of significance and 78 degrees of freedom (df), the researchers found that the t-counted (7.12) was higher than the t-table (1.66). It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. In short, the answer to the research question above is “The use of reading narrative texts can improve the ability of grade eight students of SMPN 3 Palu to identify regular and irregular verbs.